Photochemical Degradation of Bifenthrin in Water Solution - Liang, Yan-Ru; Gong, Zhen-Bin; Li, Wen-Quan (Asian Journal of Chemistry, 2013)
The mechanism of photochemical degradation of bifenthrin in water solution has been investigated using a laboratory-built photochemical degradation device hyphenated with commercial high performance liquid chromatography and UV-visible photo-spectrometric, fluorescent and mass spectrometric detector. Spectrometric characteristics of bifenthrin and its main degradation products suggest that bifenthrin could be photo-degraded under UV irradiation. The kinetics of the photochemical reaction demonstrates that laboratory-built photochemical degradation is of high efficiency for off-line degradation of interested organics. The photo-degradation reaction of bifenthrin in water solution is approximately the pseudo-first-order reaction. Mass spectrometric results show that bifenthrin is first converted into its space isomerism and then further degraded and converted to the final products under a series of molecular rearrangement, oxidation reduction and de-chlorination reaction.